Brewing Ideas: An Experience Report on the Use of World Café's to Spin on Collaborative Learning of Software Development Life Cycles - Dornelles, Pedro Lucas; Dantas, Jean; Parizi, Rafael (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2024: Anais do IV Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2024.237410, 2024)
Context: In Software Engineering Education, there is a continuous search for methods that might promote active and collaborative learning is ongoing. While many active learning strategies have been explored, few emphasize facilitating information exchange among students themselves. Goal: This study investigates the World Café technique’s effectiveness in a Software Engineering classroom, focusing on enhancing understanding of Software Development Life Cycles and fostering collaborative learning. Research Method: Over four weeks, we integrated the World Café into a Software Engineering class. We assessed (i) students’ comprehension, experiences, and perceptions of the technique’s support for learning and collaborating and (ii) the perceived usefulness, ease of use, intention of use, and potential external factors impacting the technique’s adoption. Results: Our study had 17 student participants and our findings suggest that World Café can facilitate highquality collaborative learning. Students also identified constraints like limited time, low host engagement, and inadequate discussion materials as potential challenges. Contributions and Final Remarks: This report provides insights into the World Café technique’s potential in Software Engineering Education, particularly for teaching software development life cycles and other content areas, emphasizing its potential for broader applicability.